(untitled) (Bangladesh Medical Journal, 2019)
Among the various approaches to block brachial plexus , supraclavicular approach offers a high success rate for elbow, forearm and hand surgery . Various adjuvant drugs have been used with local anesthetics in order to decrease the time of onset and prolong the duration and quality of regional blocks. So efforts were made to combine the adjuvant with local anesthetics to improve patient and surgeon satisfaction. In this randomized study we tried to see the effect of verapamil in brachial plexus block as an adjuvant with local anaesthetic .This randomized study wasconducted in Anaesthesiology department of ShaheedZiaurRahman Medical College Hospital after approved by the ethical review board of this hospital.The study subject were divided into two groups (Group A=only local anaesthetics&Group B=local anaesthetics with Verapamil) , 30 IN numbers in each group. Group-A patients was administered 15ml of 1% lignocaine with 15 ml of bupivacaine 0.25% while in Group-B patients was administered injection verapamil 3.5 ml (3.5 mg) in addition to the above mixture. In this study mean onset time of sensory block was 11.53 ± 1.4 minutes in group - A and 7.12 ± 1.68 minutes in group – B which is not statistically significant (p value = 0.057). The mean onset time of motor block in group A was 15.26 ± 1.96 min, and in group B was 11.58 ± 2.68 min and this difierence isstatistically significant (p value=0.000152). Duration of motor block was 96.30 min and 115.08 min in group A and Group B respectively. Sensory block was 157.26 min and 188.0 min in group A and Group B respectively. Regarding the heart rate, no significant difference was detected between the groups at the time of preanesthesia and at the 5 min after anaesthesia. Compared with group B patients, group A patients shows slight but statistically significant increased heart rate at the 10 min (80, 92 beat/min respectively) after brachial plexus block. At 30 minute after, mean systolic BP was 97.9±4.7 mmHg in group A and 84.3±5.0 mmHg in group B. At 45 minute after, mean systolic blood pressure was 94.6±15.6 mmHg and 84.3±5.0 mmHg in group A and group B respectively. At 60 minutes after, mean systolic blood pressure was 59.6±6.0 mmHg in group A and 61.2±9.4 mmHg in group B. At 15, 30 and 45 minute difference was statistically significant (p<0.05) between two groups. In conclusion, the study revealed that verapamil can be used as an adjuvant to decrease the onset time of sensory and motor blocks of bupivacaine in supraclavicular block. Moreover, verapamil doses in regional blocks did not show any hemodynamic side effects. Bangladesh Med J. 2017 May; 46 (2): 43-47